Platelet expression of stromal cell-derived factor-1 is associated with the degree of valvular aortic stenosis. - Thomas Wurster (PLoS ONE, 2014)
BACKGROUND AND PURPOSE: Platelet surface expression of stromal-cell-derived factor-1 (SDF-1) is increased during platelet activation and constitutes an important factor in hematopoetic progenitor cell trafficking at sites of vascular injury and ischemia. Enhanced platelet SDF-1 expression has been reported previously in patients suffering from acute coronary syndrome (ACS). We hypothesized that expression of platelet associated SDF-1 may also be influenced by calcified valvular aortic stenosis (AS). METHODS: We consecutively evaluated 941 patients, who were admitted to the emergency department with dyspnea and chest pain. Platelet surface expression of SDF-1 was determined by flow cytometry, AS was assessed using echocardiography and hemodynamic assessment by heart catheterization. A 1∶1 propensity score matching was implemented to match 218 cases with 109 pairs adjusting for age, sex, cardiovascular risk factors, and medication including ACE inhibitors, angiotensin receptor blockers, beta blockers, statins, aspirin, clopidogrel, GPIIb/IIIa antagonists, and vitamin K antagonists. RESULTS: Patients with valvular AS showed enhanced platelet SDF-1 expression compared to patients without AS (non-valvular disease, NV) independent of ACS and stable coronary artery disease (SAP) [mean fluorescence intensity (MFI) for ACS (AS vs. NV): 75±40.4 vs. 39.5±23.3; P = 0.002; for SAP (AS vs. NV): 54.9±44.6 vs. 24.3±11.2; P = 0.008]. Moreover, the degree of AS significantly correlated with SDF-1 platelet surface expression (r = 0.462; P = 0.002). CONCLUSIONS: Valvular AS is associated with enhanced platelet-SDF-1 expression; moreover the degree of valvular AS correlates with SDF-1 platelet surface expression. These findings may have clinical implications in the future.